Penerapan Data Mining Apriori Pada Persediaan Obat (Studi Kasus Apotek Rafif Farma Medan) - Mardiah Mardiah (UIN Sumatera Utara, 2019)
The importance of inventory systems at a pharmacy and the type of goods whichare a top priority that must be in stock. It is useful to anticipate the void stuff. Due to thelack of inventory may affect customer service and asset to the pharmacy. Therefore, thisstudy was conducted to help resolve those problems by designing a data miningapplication that serves to predict sales of the drug is needed most knowable a priorialgorithm with the help of Tools Tanagra. One of the interesting association analysisphase analysis algorithm that generates a high frequency patterns (frequent patternmining).Keywords: Data Mining, Apriori Algorithm, Association Rule